Local flap therapy for the treatment of pressure sore wounds. Issue 5 (17th October 2013) - Wettstein, Reto; Tremp, Mathias; Baumberger, Michael; Schaefer, Dirk J; Kalbermatten, Daniel F
Abstract: The aim of this study was to analyse the effectiveness of an interdisciplinary cooperation between conservative and surgical disciplines for the treatment of pressure sores (PS). From January 2004 to December 2005, a single‐centre study was performed with paraplegic and tetraplegic patients presenting with PS grades III–V. Outcome measures were defect size, grade, method of reconstruction, complication and recurrence rate as well as average length of hospitalisation. A total of 119 patients aged 22–84 years with totally 170 PS were included. The most common PS were located in the ischial region (47%), followed by the sacral (18%), trochanteric (11%), foot (9%) and the malleolar (8%) regions. Defect sizes ranged between 4 and 255 cm 2 . Grade IV was the most common PS (68%), followed by grade III (30%) and grade V (2%) PS. For wound closure, fasciocutaneous flaps were used most frequently (71%), followed by skin grafts (10%) and myocutaneous flaps (7%). Postoperative follow‐up ranged between 6 and 38 months. The overall complication and recurrence rate was 26% and 11%, respectively. If no complication occurred, the average duration of hospitalisation stay after the first debridement was 98 ± 62 days. In conclusion, our treatment concept is reliable, effective and results in a low recurrence rate. The complication rate, even though favourable when compared with the literature, still needs to be improved.